Dental School Vacant Budgeted Faculty Positions, Academic Years 2011–12 Through 2013–14. Issue 10 (1st October 2015) - Wanchek, Tanya; Cook, Bryan J.; Anderson, Eugene L.; Duranleau, Lauren; Valachovic, Richard W.
Abstract : The American Dental Education Association (ADEA) Survey of Dental School Faculty is conducted annually to provide an overview of the hiring and retention activity of U.S. dental school faculty. The survey collects data on the dental faculty workforce, including vacant budgeted positions by appointment and discipline, number of new and lost positions, sources of new hires, and reasons for faculty separations. This report highlights the results of three years of survey data, from the 2011–12 academic year through the 2013–14 academic year. After declining in previous years, the number of vacant faculty positions in U.S. dental schools has begun to increase, rising to 242 full‐time and 55 part‐time positions in 2013–14. Additionally, the number of schools having more than ten vacancies increased from five to 12. Although the number of vacancies has increased, the length of faculty searches that took more than one year declined from 25% to 16% in the same period. Retirements as a share of full‐time faculty separations increased from 14% in 2008–09 to 31% in 2013–14. The current average retirement age of dental school faculty members is 69.7 years. The percentage of full‐time faculty members leaving for the private sector remained constant over the last three years at approximately 16%. Full‐time faculty members were more likely to be recruited from other dental schools, while part‐time faculty members were more likely to come from the private sector.